Generation of Multiple-Frequency Optical Millimeter-Wave Signal With Optical Carrier Suppression and No Optical Filter - Ying Zhang; Bo Liu; Sai Ji (IEEE Photonics Journal, 2017)
We propose and experimentally demonstrate the generation of a multiple-frequency optical millimeter-wave (mm-wave) signal an without optical filter at the transmitter side. Forty, 80, and 120-GHz multiple-frequency optical mm-wave signals are generated simultaneously in our experiment. After 20 km standard single-mode fiber transmission, high-quality eye diagrams with large opening and high stability are obtained at these frequency bands.